A mapping of health services in the care network of Augusto Corrêa city (REMUNOM, 2024)
This study aims to present a situational diagnosis of the assistance network of the health system in the municipality of Augusto Corrêa, located in the northeast of Pará. A mapping of the health services offered in the municipality was carried out, through the identification of health structures, which can serve as reference and counter-reference. In order to carry out this mapping, internal control data were collected in the municipal secretariats, and public data provided by DATASUS. The data were tabulated, in a targeted and simplified way, to facilitate access to users later. The units were located on Google Maps and markers were inserted for their respective identification. In total, there was 34 units providing health services in the municipality, 19 of which are located in urban areas and 15 in rural areas. It is concluded that the municipality has a large coverage of units providing health services, with an average of 3039 users per unit in the urban area, and 1483 users per unit in the rural area. In all, there were 16 dentists, resulting in a average of 2531 inhabitants per professional; as well as 40 doctors, generating an average of 1011 inhabitants per professional; and 37 nurses, with 1,097 inhabitants per professional.